Determination of thermal field frequency for aerospace materials using infrared thermography technology - Yang, Bin (2013)
This report describes an investigation of the thermal Hartmann wavefront sensing method in the determination of the Thermal Field Frequency. As proven by a previous experiment in SIMTech, the combination of the thermal Hartmann method uses the reconstructed thermal wavefront to inspect the presence of defects instead of measuring the surface temperature of the composite under inspection. This improves the detectability, the imaging quality and can determine the defects precisely. However there is a fixed fluctuation which was also found during the previous experiment. To study the fluctuation, an experiment based on thermal wavefront sensing technology was setup and a series of experiments was performed.